Analisis Program (Dapur Sehat Atasi Stunting) DASHAT dalam Percepatan Penurunan Stunting (Studi Kasus Kampung KB Berkah Bersama) - Suci Sya’bani; Daeng Ayub; Dafetta Fitrilinda (Journal of Management Education Social Sciences Information and Religion, 2024)
In many countries, including Indonesia, stunting is a public health problem. The Quality Family Village DASHAT (Healthy Kitchens Overcome Stunting) program has become one of the activities in the effort to reduce stunting. In this article, qualitative methods are used to collect data through observation, interviews and documentation studies. This article also refers to related scientific literature, the latest statistical data, as well as documents and reports related to child health and community empowerment in the Berkah Bersama Quality Family Village. The research results also show the success of this program in supporting stunting reduction and provide important insight into the development of this program in efforts to accelerate stunting reduction in Indonesia. The implications of this research can help improve and develop this program and similar initiatives in other countries facing similar problems in terms of stunting and child nutrition.